EXPLORING ENGLISH TEACHERS’ PERCEPTIONS OF AI CHATBOTS IN ENGLISH LANGUAGE INSTRUCTION: A CASE STUDY AT DONG NAI UNIVERSITY - NGUYEN THI LOAN (Tạp chí Khoa học xã hội Thành phố Hồ Chí Minh, 2025)
The rapid advancement of artificial intelligence (AI) has encouraged the adoption of AI-powered chatbots in English as a Foreign Language (EFL) classrooms. This study explores English teachers’ perceptions of the opportunities and challenges of using chatbots in English instruction at Dong Nai University, Vietnam. A mixed-methods design was employed, combining a quantitative online survey of 112 teachers and semi-structured interviews with 18 participants. The findings reveal that most teachers hold positive attitudes toward chatbots, acknowledging their potential to enhance learner engagement, support autonomous learning, and provide immediate feedback. However, several challenges were identified, including concerns about content accuracy, curriculum alignment, ethical data use, and teachers’ limited digital competence. The qualitative insights highlight the need for pedagogical training, technical assistance, and institutional policies to facilitate effective integration. While teachers expressed strong interest in implementing chatbots, many remained cautious due to inadequate training and institutional support. This study contributes to the growing literature on AI in language education by emphasizing teachers’ voices and offering practical recommendations for teacher development and policy planning to promote AI literacy and sustainable technology integration in EFL teaching.